NH3/NH4+ allosterically activates SLC4A11 by causing an acidic shift in the intracellular pK that governs H+(OH−) conductance - Pasternack, Richard A.; Quade, Bianca N.; Marshall, Aniko; Parker, Mark D. (Frontiers in Physiology, 2024)
SLC4A11 is the most abundant membrane transport protein in corneal endothelial cells. Its functional presence is necessary to support the endothelial fluid pump that draws fluid from the corneal stroma, preventing corneal edema. Several molecular actions have been proposed for SLC4A11 including H2O transport and cell adhesion. One of the most reproduced actions that SLC4A11 mediates is a H + (or OH -) conductance that is enhanced in the presence of NH4Cl. The mechanism by which this occurs is controversial with some providing evidence in favor of NH3-H + cotransport and others providing evidence for uncoupled H + transport that is indirectly stimulated by the effects of NH4Cl upon intracellular pH and membrane potential. In the present study we provide new evidence and revisit previous studies, to support a model in which NH4Cl causes direct allosteric activation of SLC4A11 by means of an acidic shift in the intracellular pK (pKi) that governs the relationship between intracellular pH (pHi) and SLC4A11 H + -conductance. These findings have important implications for the assignment of a physiological role for SLC4A11.